Solid Catalysts and theirs Application in Biodiesel Production - Ramli Mat; Rubyatul A. Samsudin; Mahadhir Mohamed; Anwar Johari (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2012)
The reduction of oil resources and increasing petroleum price has led to the search for alternative fuel from renewable resources such as biodiesel. Currently biodiesel is produced from vegetable oil using liquid catalysts. Replacement of liquid catalysts with solid catalysts would greatly solve the problems associated with expensive separation methods and corrosion problems, yielding to a cleaner product and greatly decreasing the cost of biodiesel production. In this paper, the development of solid catalysts and its catalytic activity are reviewed. Solid catalysts are able to perform trans-esterification and esterification reactions simultaneously and able to convert low quality oils with high amount of Free Fatty Acids. The parameters that effect the production of biodiesel are discussed in this paper. © 2012 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)